Organizational Socialization Leadership Behaviors and Organizational Culture in Student Affairs Department, Universiti Utara Malaysia - Noor Hapisah, Mangsor (2011)
The purpose of this study is to look into the theories regarding leadership behavior, organizational culture, and organizational socialization. Use the 298 questionnaire, was distribute to the Student Affairs Department. Following personal data collection performed during one-to-one research session with respondents, quantitative statistical analysis were carried out and the descriptive analysis were performed, the relation between the variables were examine use multiple regression. The result offer insight for managers to identify opportunities for future empirical research on change initiative in organization.